INTERNALISASI KARAKTER MANDIRI SISWA DALAM PEMBELAJARAN LITERASI SAINS - El-Islami, Ikhwan Nur Hakim; Miftachudin; Muttaqin, Muhammad Fauzan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the process of internalization of students' independent character in science literacy learning. The approach used is qualitative research with a case study method. The subjects of the study consisted of grade VI students at SDIT Yasir Tangerang. Data collection was carried out through direct observation in class, in-depth interviews with teachers and students, and document analysis such as learning notes and student assignment results. Data validity uses source and method triangulation techniques. Data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that internalization of independence in science literacy learning at SDIT Yasir has a positive impact on students' academic and character development. Students involved in exploratory learning methods show increased self-confidence, courage in expressing opinions, and initiative to find additional learning resources. However, there are still challenges in implementing independence, especially for students who are more dependent on teacher direction. The suggestion is that a differentiation approach in learning needs to be applied to adjust to students' needs.